2015
DOI: 10.1007/s00701-015-2585-3
|View full text |Cite
|
Sign up to set email alerts
|

Experiences on two different stereotactic radiosurgery modalities of Gamma Knife and Cyberknife in treating brain metastases

Abstract: Despite slightly inferior dosimetric properties of CK, fractionated CK for large BMs appears to be as effective and safe as single-fraction GK for small BMs, representing fractionation as an effective strategy for enhancing efficacy and moderating toxicity in stereotactic radiosurgery for BMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…These “reference” schedules ranged between 6-7 Gy × 5 and 7-10Gyx3. [ 4 13 18 19 20 36 43 44 46 ] Prescription doses to tumor margins were set at lower isodose lines (usually at the 35%-40% lines) to (i) match local target conformity aspects, (ii) increase the average dose inside the tumor, and (iii) optimize 10 Gy-volume increment at each GKRS. Taking into account the possible limitations of the LQ-formalism, isoeffective conversions[ 1 26 41 42 ] were used to (i) identify bearable/minimally toxic biologically effective dose distributions outside tumor margins using an alpha/beta ratio of 2-2.5 for normal brain tissue and (ii) set a customized Baseline Ablative Isodose Line (BAIL) adjusted to the tumor's potential alpha/beta ratio.…”
Section: Discussionmentioning
confidence: 99%
“…These “reference” schedules ranged between 6-7 Gy × 5 and 7-10Gyx3. [ 4 13 18 19 20 36 43 44 46 ] Prescription doses to tumor margins were set at lower isodose lines (usually at the 35%-40% lines) to (i) match local target conformity aspects, (ii) increase the average dose inside the tumor, and (iii) optimize 10 Gy-volume increment at each GKRS. Taking into account the possible limitations of the LQ-formalism, isoeffective conversions[ 1 26 41 42 ] were used to (i) identify bearable/minimally toxic biologically effective dose distributions outside tumor margins using an alpha/beta ratio of 2-2.5 for normal brain tissue and (ii) set a customized Baseline Ablative Isodose Line (BAIL) adjusted to the tumor's potential alpha/beta ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Lehrer et al made an international meta‐analysis of trials and found that HFSRT offered a relative reduction of radionecrosis while maintaining or improving 1‐year local control rate when compared to SRS. Therefore, HFSRT is effective to treat brain metastases, associates with better local control and reduces risk of radionecrosis as compared with SRS …”
Section: Introductionmentioning
confidence: 99%
“…The technical characteristics of Leksell Gamma Knife ® (Schell et al 1995) and CyberKnife ® (Dieterich et al 2011), covering both these aspects, make them elective modalities for that purpose. On the other side, due to the improvement of image guided delivery techniques, linac based protocols are also quite widespread (Wowra et al 2009, Treuer et al 2014, Cho et al 2015, Frakes et al 2015, Park et al 2016. In this framework the dose delivery method that characterizes helical TomoTherapy ® (HT) (Langen et al 2010) systems could potentially provide an efficient and accurate alternative to the previously mentioned techniques.…”
Section: Introductionmentioning
confidence: 99%